Optical properties of defects in nitride semiconductors. Issue 20 (23rd September 2015) - Tischer, Ingo; Hocker, Matthias; Neuschl, Benjamin; Madel, Manfred; Feneberg, Martin; Schirra, Martin; Frey, Manuel; Knab, Manuel; Maier, Pascal; Wunderer, Thomas; Leute, Robert A.R.; Wang, Junjun; et al.
Abstract: Abstract : Group III nitrides are promising materials for light emitting diodes (LEDs). The occurrence of structural defects strongly affects the efficiency of these LEDs. We investigate the optical properties of basal plane stacking faults (BFSs), and the assignment of specific spectral features to distinct defect types by direct correlation of localized emission bands measured by cathodoluminescence in a scanning electron microscope with defects found in high resolution (scanning) transmission electron microscopy and electron beam induced current at identical sample spots. Thus, we are able to model the electronic structure of BSFs addressing I1, I2, and E type BSFs in GaN and AlGaN with low Al content. We find hints that BSFs in semipolar AlGaN layers cause local changes of the Al content, which strongly affects the usability of AlGaN as an electron blocking layer in nitride based LEDs.